Performance Analysis of Inclusive Learning Support System and Adaptive Curriculum Development on Academic Success and Independence of Students with Disabilities in Central Java - Loso Judijanto; Salwa Aulia Novitasari; Muhamad Ammar Muhtadi (Westscience Press, 2024)
This study investigates the performance of inclusive learning support systems and adaptive curriculum development on the academic success and independence of students with disabilities in Central Java, Indonesia. A quantitative research approach was employed, with data collected from 125 participants representing students, teachers, parents, and educational professionals involved in inclusive education programs. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) path modeling was utilized to analyze the data. The measurement model demonstrated strong reliability and validity, while the structural model revealed significant positive relationships between inclusive education strategies, academic success, and independence of students. Discriminant validity was established, and the estimated model demonstrated acceptable fit and predictive relevance. Regression results further supported the positive impact of inclusive learning support systems and adaptive curriculum development on the academic success and independence of students. Overall, the findings highlight the importance of inclusive education practices in promoting positive outcomes for students with disabilities and underscore the need for continued efforts to enhance the inclusivity and effectiveness of educational programs in Central Java.